Large-scale shaking table test and numerical analysis of seismic performance of geocell retaining wall - Jin, Feifei (Frontiers in Earth Science, 2025)
Large-scale shaking table model tests were conducted to investigate the seismic performance of geocell retaining walls. The variation laws of lateral confinement pressure, acceleration amplification factor, horizontal displacement of wall and settlement of slope under different ground motion parameters are analyzed, and the failure mode of retaining wall is discussed. At the same time, FLAC3D numerical software is used to establish and analyze the slope ratio and height width ratio of retaining wall. The following conclusions are derived from the aforementioned data: (1) The results indicate that as seismic amplitude increases, the lateral confinement pressure within the cells, the peak horizontal displacement, and the slope crest settlement all increase gradually. Furthermore, the acceleration amplification coefficient exhibits an amplification effect along the elevation. (2) When the frequency is less than 4 Hz, the geocell lateral confinement pressure, acceleration amplification factor, and slope settlement are relatively small, and displacement decreases with increasing frequency. Conversely, when the frequency exceeds 4 Hz, the four seismic indices increase pro-gressively. (3) The dynamic response of the model is more pronounced under X-direction vibrations, and natural waves have a greater impact on the model. (4) After vibration at an amplitude of 0.9 g concludes, the non-uniform settlement value is 0.593%, which is below the 2% wall height recommended by specifications, demonstrating excellent settlement control capability. (5)When the amplitude exceeds 0.5 g (i.e., seismic intensity greater than VI degrees), reinforcement belts should be added at the 3H/16 and 8H/16 positions to enhance the stability of the retaining wall. (6) Upon completion of the 1.0 g amplitude test, the permanent horizontal displacement of the retaining wall measures 31.58 mm, accounting for 1.97% of the wall height—below the 2% limit specified by AASHTO standards and thus not meeting the failure criteria. (7) The failure process of the retaining wall can be divided into three stages: vibration compaction, intensified deformation, and convex sliding. After the entire vibration ended, no large-scale collapse or other phenomena occurred in the wall, and it has good seismic performance. (8) Reducing the slope ratio and aspect ratio of the retaining wall significantly improves its stability, and these parameters can be prioritized to 1:0.3 and 1.8, to meet seismic requirements while conserving resources. (9) These findings provide valuable references for the seismic design of geocell retaining wall structures.